2020
DOI: 10.1021/acs.jpcb.0c00551
|View full text |Cite
|
Sign up to set email alerts
|

Microheterogeneity in Aqueous Acetonitrile Solution Probed by Soft X-ray Absorption Spectroscopy

Abstract: Chemical processes in solution are influenced by microheterogeneity (MH), where two liquids seem to be mixed in a macroscopic scale but are microscopically inhomogeneous. We have investigated one of the simplest MH systems, aqueous acetonitrile solution, using soft X-ray absorption spectroscopy (XAS). Molecular interactions of acetonitrile were revealed by C and N Kedge XAS at different concentrations, and those of solvent water were separately revealed by O Kedge XAS. The energy shift of the CN π* peak at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 56 publications
1
25
0
1
Order By: Relevance
“…The interaction among these compounds are summarized in Figure d. Clusters of AcOH would be formed in liquid DMS, as observed in aqueous acetonitrile solution . On the other hand, AcOH is mixed with MeOH on a microscopic scale owing to the strong interaction of AcOH with MeOH.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The interaction among these compounds are summarized in Figure d. Clusters of AcOH would be formed in liquid DMS, as observed in aqueous acetonitrile solution . On the other hand, AcOH is mixed with MeOH on a microscopic scale owing to the strong interaction of AcOH with MeOH.…”
Section: Resultsmentioning
confidence: 88%
“…Clusters of AcOH would be formed in liquid DMS, as observed in aqueous acetonitrile solution. 13 On the other hand, AcOH is mixed with MeOH on a microscopic scale owing to the strong interaction of AcOH with MeOH. These soft X-ray absorption experiments led us to conclude that MeOH would break the interaction of AcOH− AcOH pairs in the AcOH clusters and help the formation of the AcOH−DMS pairs on a microscopic scale, which could accelerate the reaction of AcOH and DMS.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…57,59 A recent soft X-ray absorption spectroscopic study of W/AN mixtures presented evidence of microheterogeneity. 61 Ab initio quantum chemical inner-shell calculations suggested that the three distinct regions observed in these mixtures result from the interplay of hydrogen bonding and dipolar interactions between water and acetonitrile molecules. 61 Notably, the discontinuity observed at ≈13 vol % W (molar fraction of water x w = 0.3) was ascribed to a transition between phases mainly containing AN-rich large W n AN m clusters below x w = 0.3 and smaller clusters held by dipolar interactions above x w = 0.3.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Notably, the discontinuity observed at  13 vol % W (molar fraction of water x w = 0.3) was ascribed to a transition between phases mainly containing AN-rich large W n AN m clusters below x w = 0.3 and smaller clusters held by dipolar interactions above x w = 0.3. 61 We believe that the dramatic increase of -HH persistence below 20 vol % W is associated with such phase-transition. clusters.…”
Section: Table 1-rate Coefficients Of -Hhs Decay In Water:acetonitrimentioning
confidence: 86%
“…The liquid layer is sandwiched between two Si 3 N 4 membranes and the liquid thickness is controllable from 2000 nm to 20 nm by controlling the helium pressure around the liquid cell from 0.1 MPa to 0.12 MPa (Nagasaka et al, 2018a). In aqueous solutions, molecular interactions of solute organic molecules are measured by C and N K-edge XAS, and those of water are separately observed by O K-edge XAS (Nagasaka et al, 2018b(Nagasaka et al, , 2020b. XAS is also applied to in situ/operando observations of catalytic (Yuzawa et al, 2015) and electrochemical reactions (Nagasaka et al, 2013(Nagasaka et al, , 2014.…”
Section: Introductionmentioning
confidence: 99%